Tropical cyclone intensity modulated by the oceanic eddies in the Bay of Bengal - Navaneeth Kodunthirapully Narayanaswami; Venkatesan Ramasamy (Oceanologia, 2022)
The Bay of Bengal, an affluent region for mesoscale oceanic eddies, is also home to devastating tropical cyclones. The intensity modulation of two cyclones, Phailin (2013) and Fani (2019), in the Bay of Bengal by the oceanic eddies is studied. The intensities of both the cyclones rapidly changed after transiting over mesoscale eddies. The surface and subsurface oceanic conditions before and during the passage of the two cyclones were analysed. During Phailin (Fani), the cyclonic (anticyclonic) eddy resulted in significant (weak) sea surface temperature cooling due to the shallow (deep) D26 isotherm. Wind shear estimates revealed that it had no (minor) effect on the weakening (intensification) of Phailin (Fani). The analysis of enthalpy fluxes during the two cyclones has shown that during Phailin (Fani), the latent heat flux supply was reduced (enhanced) by 20 W m−2 (30 W m−2) over the regions of the cyclonic (anticyclonic) eddy due to significant (weak) sea surface temperature cooling. The case study of cyclone interaction with mesoscale oceanic eddies has shown that a thorough understanding of mesoscale eddies is vital for improving the accuracy of the cyclone intensity forecasts.